The cruel dawn [large type] - Hall, Rachel Howzell (Hall, Rachel Howzell. Vallendor duology, 2025)
Kaivara Megidrail was once worshipped as the Grand Defender of Vallendor -- until betrayal, punishment, and exile left her Diminished. Now, the realm she abandoned teeters on the edge of collapse. Monsters roam free. Gods whisper in shadows. And one man -- Jadon Wake, prince, blacksmith, liar -- may be the key to her salvation ... or her final ruin. Haunted by the past, hunted by divine enemies, and armed with only fractured Memories and an unrelenting will, Kaivara must choose: reclaim her power and face the truth about Jadon, or watch Vallendor fall to a traitorous god's rising.